Preliminary Hybrid Modeling of the Panama Canal: Operations and Salinity Diffusion. (12th April 2012) - Rabelo Rabelo, Luis Luis; Marin Marin, Mario Mario; Xanthopoulos Xanthopoulos, Petros Petros; Arellano Lennox Arellano Lennox, Carlos Carlos; Coiduras Coiduras, Pedro Pedro; Campos Campos, Bernardo Bernardo; Andrade Andrade, Luz Luz; Collins Collins, Ricardo Ricardo; Atencio Atencio, Erwin Erwin; Pitty Pitty, Daryelis Daryelis
Abstract : This paper deals with the initial modeling of water salinity and its diffusion into the lakes during lock operation on the Panama Canal. A hybrid operational model was implemented using the AnyLogic software simulation environment. This was accomplished by generating an operational discrete-event simulation model and a continuous simulation model based on differential equations, which modeled the salinity diffusion in the lakes. This paper presents that unique application and includes the effective integration of lock operations and its impact on the environment.